Pengaruh Budaya Organisasi Terhadap Kepuasan Kerja Karyawan di Grand Q Hotel Gorontalo - Husain, Yeristiawati (Tulisan Ilmiah Pariwisata (TULIP), 2024)
In the development of an organization, culture is the most important variable thataffects the implementation of organizational operation, because it’s culture may stimulate the job satisfaction of its human resource which in turn affects the achievement of the organization’s goals.Therefore, the objective of the research was to find out the conditions of both organizational culture and job satisfaction of employees at Grand Q Hotel Gorontalo. The research method used was a descriptive-quantitative survey method by a sample of 55 employees at Grand Q Hotel Gorontalo. The research used a multiple linear regression analysis. The research result showed that, simultaneously, organizational culture has a strong influence by 94.3% on job satisfaction (Y), the remaining 5.7% being the contribution of other variables beyond the current research. That is, the stronger culture, the higher job satisfaction will be. In contrary, the weaker culture, the lower job satisfaction will be.